Lyocell/silver knitted fabrics for prospective diabetic foot ulcers treatment: effect of knitting structure on bacteria and cell viability - Tavares, Tânia Daniela Eugénio (2025)
Diabetic foot ulcers (DFUs) are a serious complication of diabetes, often resulting in infections and further health deterioration. Thus, the development of an approach combining different therapies in just one formulation to treat DFUs remains very challenging. Silver-plated polyamide fibers offer antimicrobial properties, while lyocell provides biodegradability, biocompatibility and moisture management abilities. In this sense, the present study explores the potential of lyocell/silver-plated polyamide fabrics as part of advanced wound dressings designed to improve DFU treatment. The most common knitting structures, namely single jersey, false rib 1×1, single pique, and false interlock, were selected for combining the yarns and successfully processed using seamless technology. The knitted fabrics were then subjected to a comprehensive analysis of their physical, chemical, and thermomechanical properties, demonstrating that the samples met the criteria for effective wound dressing development. Their antimicrobial efficacy was evaluated against DFU-associated Gram-negative pathogens, Escherichia coli and Pseudomonas aeruginosa, showing strong antimicrobial activity for up to 24h, with total inhibition in some cases (jersey, pique and interlock structures for E. coli and interlock structure for P. aeruginosa). Antioxidant testing revealed DPPH reduction of 61.7±14.4%. Biocompatibility was assessed using keratinocytes HaCaT cell lines, showing that knitted fabrics with up to 1.46% silver content did not harm mammalian cells. In general, interlock structure revealed the most promising features, including mechanical performance, and air and water vapor permeability, for promoting optimal wound healing conditions.